2007
DOI: 10.1210/me.2007-0150
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and Genetic Analysis of Biomarkers for Peroxisome Proliferator-Activated Receptor α Expression and Activation

Abstract: Peroxisome proliferator-activated receptor alpha (PPARalpha) is a nuclear receptor with manifold effects on intermediary metabolism. To define a set of urinary biomarkers that could be used to determine the efficacy of PPARalpha agonists, a metabolomic investigation was undertaken in wild-type and Pparalpha-null mice fed for 2 wk either a regular diet or a diet containing the PPARalpha ligand Wy-14,643 ([4-chloro-6-(2,3-xylidino)-2-pyrimidinylthio] acetic acid), and their urine was analyzed by ultra-performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 28 publications
6
72
0
Order By: Relevance
“…Variations of this compound have been observed in previous metabolomics studies (Li et al 2013;Zhen et al 2007). …”
Section: Biological Interpretationsupporting
confidence: 62%
See 1 more Smart Citation
“…Variations of this compound have been observed in previous metabolomics studies (Li et al 2013;Zhen et al 2007). …”
Section: Biological Interpretationsupporting
confidence: 62%
“…This compound was significantly elevated in the urine of mice treated with a peroxisome proliferator-activated receptor (PPARα) agonist, suggesting that this metabolite could be a potential urinary biomarker of PPARα agonists (Zhen et al 2007). In this context, the activation of PPARα through diet or by synthetic agonists may cause an improvement in lipid profile and by extension impact on cardiovascular health.…”
Section: Biological Interpretationmentioning
confidence: 99%
“…A recent metabolomic study observed several nicotinamide metabolites to be elevated in the urine of both T2DM rodents and T2DM humans. Interestingly, these metabolites were also reported to be biomarkers for peroxisome proliferator-activated receptor ␣ activation (10,65,66). Given the clear role of peroxisome proliferator-activated receptor ␣ and its family members in fatty acid metabolism, pipecolic acid and nicotinamide metabolites as diagnostic biomarkers for T2DM in human patients should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the power of mass spectrometry-based metabolomics to profi le metabolic pathways to reveal the mechanism of action of nuclear receptors and the metabolic fate of drugs (9)(10)(11)(12). Metabolomics has revealed the downregulated tryptophan-nicotinamide pathways following Wy-14,643 treatment ( 9 ) and the decreased excretion of carnitine-conjugated metabolites by fenofi brate treatment in humans ( 13 ).…”
Section: Identifi Cation and Quantitation Of Urinary And Serum Metabomentioning
confidence: 99%
“…Metabolomics has revealed the downregulated tryptophan-nicotinamide pathways following Wy-14,643 treatment ( 9 ) and the decreased excretion of carnitine-conjugated metabolites by fenofi brate treatment in humans ( 13 ). Furthermore, an increase in the excretion of glycine conjugated metabolites was observed in Ppara -null mice ( 9 ), and the long-chain fatty acid carnitines, including palmitoylcaritine, myristolcarnitine, oleoylcarnitine, and palmitoleoylcarnitine, were elevated in the serum after suppression of PPAR␣ signal transduction by acetaminophen ( 14 ).…”
Section: Identifi Cation and Quantitation Of Urinary And Serum Metabomentioning
confidence: 99%